Reflections on the 'discovery' of the anti-malarial qinghao - Hsu, E (Blackwell Publishing Ltd., 2006)
Artemisinin, qinghaosu, was extracted from the traditional Chinese medical drug qinghao (the blue-green herb) in the early 1970s. Its 'discovery' can thus be hailed as an achievement of research groups who were paradoxically successful, working as they were at the height of political mass movement in communist China, known in the West as the Cultural Revolution (1966-1976), a period that was marked by chaos, cruelty and enormous suffering, particularly, but by no means only, among the intelligentsia. On the one hand, China's cultural heritage was seen as a hindrance to progress and Mao set out to destroy it, but on the other hand he praised it as a 'treasure house', full of gems that, if adjusted to the demands of contemporary society, could be used 'for serving the people' (wei renmin fuwu). The success of the 'task of combating malaria' (kang nüe ren wu), sometimes know as 'task number five hundred and twenty-three', depended crucially on modern scientists who took seriously knowledge that was recorded in a traditional Chinese medical text, Emergency Prescriptions Kept up one's Sleeve by the famous physician Ge Hong (284-363).